2007
DOI: 10.2527/jas.2006-116
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of high-digestible sorghum for pigs and broiler chicks1

Abstract: Two experiments were conducted to evaluate the nutritional quality of 2 varieties of Purdue high-digestible sorghum (PHD1 and PHD2) and a normal sorghum, compared with corn, in diets of pigs and broiler chicks. In Exp. 1, 12 pigs (average BW, 55 kg) fitted with ileal T-cannula were fed 4 diets containing 946 g of corn or sorghum (PHD1, PHD2, and normal) per kg in a 2-period crossover design (i.e., each pig received 2 diets over a 2-wk period with 6 pigs per dietary treatment) to determine apparent ileal or tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 18 publications
4
14
0
4
Order By: Relevance
“…Despite the improvement in in vitro protein digestibility of these high protein digestibility sorghum lines, animal feeding trails with pigs and broiler chickens did not show any improvement compared to maize or normal sorghum in important digestibility parameters (Nyannor et al, 2007). High protein digestibility sorghum flour has, however, been shown give better dough properties (resistance to extension and time to dough breakage) and higher bread loaf volumes than normal sorghum when composited with wheat flour (Goodall et al, 2012).…”
Section: Proteinmentioning
confidence: 94%
“…Despite the improvement in in vitro protein digestibility of these high protein digestibility sorghum lines, animal feeding trails with pigs and broiler chickens did not show any improvement compared to maize or normal sorghum in important digestibility parameters (Nyannor et al, 2007). High protein digestibility sorghum flour has, however, been shown give better dough properties (resistance to extension and time to dough breakage) and higher bread loaf volumes than normal sorghum when composited with wheat flour (Goodall et al, 2012).…”
Section: Proteinmentioning
confidence: 94%
“…The numerical increments of dry matter intake as an increasing level of sorghum is might be due to the low amount of crude fiber and slightly higher amount of energy and protein contents. Similarly, Nyannor et al [18] reported no difference in feed consumption of chicks fed high digestible sorghum from 1 to 21 days of growing period. The result of the current study generally support that research conducted in Kenya replacement of sorghum for maize up to 40 percent did not significantly vary [19].…”
Section: Dry Matter Intakementioning
confidence: 99%
“…Roughly, 90% of the world"s guinea corn area lie in the developing countries, mainly in Africa and Asia (FAO, 1996). These crops are primarily grown in poor areas subject to low rainfall and drought where other grains are unsuitable for production unless irrigation is available (Nyannor et al, 2007). Guinea-corn is widely grown both for food and as a feed grain and it constitute a major source of calories and protein for millions of people in Africa and Asia.…”
Section: Guinea Corn and Its Cultivationmentioning
confidence: 99%